Continuous Tremor Activity With Stable Polarization Direction Following the 2014 Large Slow Slip Event in the Hikurangi Subduction Margin Offshore New Zealand. Issue 2 (17th February 2022) - Iwasaki, Yuriko; Mochizuki, Kimihiro; Ishise, Motoko; Todd, Erin K.; Schwartz, Susan Y.; Zal, Hubert; Savage, Martha K.; Henrys, Stuart; Sheehan, Anne F.; Ito, Yoshihiro; Wallace, Laura M.; Webb, Spahr C.; et al.
Abstract: Many types of slow earthquakes have been discovered at subduction zones around the world. However, the physical process of these slow earthquakes is not well understood. To monitor offshore slow earthquakes, a marine seismic and geodetic experiment was conducted at the Hikurangi subduction margin from May 2014 to June 2015. During this experiment, a large slow slip event (Mw 6.8) occurred directly beneath the ocean bottom seismometer (OBS) network. In this study, S‐wave splitting and polarization analysis methods, which have been previously used on onshore data to investigate tremor and anisotropy, are applied to continuous OBS waveform data to identify tremors that are too small to detect by the envelope cross correlation method. Continuous tremor activity with stable polarization directions is detected at the end of the 2014 slow slip event and continued for about 2 weeks. The tremors are generated around a southwest bend in the slow slip contours and at the landward edge of a subducted seamount. Our findings corroborate a previous interpretation, based on burst‐type repeating earthquakes and intermittent tremor, that localized slow slip and tremor around the seamount was triggered by fluid migration following the large plate boundary slow slip event and indicate tremor occurred continuously rather than as isolated and sporadic individual events. Plain Language Summary: Slow earthquakes and tremor are characterized by slow fault rupture. Their generation mechanism has not been well understood. The slow earthquake itself does not cause damage but may inform forecasts of large earthquakes that could cause strong ground shaking or tsunamis. A large slow slip event occurred on the Hikurangi subduction plate boundary, offshore New Zealand, in 2014 directly beneath a temporary ocean bottom seismometer network. We applied new methods to this data to detect and characterize an earthquake tremor signal. The methods determine the polarization of the wave emanating from the tremor and the fast direction of the anisotropic subsurface structure through which the tremor wave propagates. These parameters enable us to detect small amplitude tremors and to determine their spatial and temporal distribution. We observed continuous tremor activity for about 2 weeks duration while the slow slip event was waning. This tremor activity occurred over a mapped subducted seamount and on the plate boundary, which likely experienced large stress changes due to the slow slip event. Our results are consistent with previous studies that used different methods on the same data, which indicate that the tremor activity in the vicinity of the seamount was triggered by fluid migration. Key Points: S‐wave splitting and polarization analyses of continuous offshore data detect small amplitude tremor activity Tremor activity with stable polarization direction started near the end of the 2014 Gisborne slow slip event (SSE) and was continuous for about 2 weeks Tremor activity occurred around the landward edge of the subducted seamount and was triggered by fluid migration following the SSE